Automatic Intra-/Extra-Dimensional Attentional Set-Shifting Task in Adolescent Mice - Ciampoli, Mariasole; Scheggia, Diego; Papaleo, Francesco (Frontiers in Behavioral Neuroscience, 2021)
Adolescence is a developmental period crucial for the maturation of higher order cognitive functions. Indeed, adolescence deficits in executive functions are strong predictors of increased vulnerability to several mental disabilities later in life. Here, we tested adolescent mice in a fully-automated attentional set shifting task equivalent to the humans’ Wisconsin Card Sorting Test and the Cambridge Neuropsychological Test Automated Battery Intra-/Extra-Dimensional set-shift task (ID/ED). Compared to adult, adolescent mice required more time to complete the task (≈16 days), and a higher percentage failed to finish the entire task. Nevertheless, adolescent mice completing this demanding task showed an increased effort in solving the extradimensional shift stage (EDS) compared to previous stages. Moreover, we found that this paradigm can be used to detect early cognitive dysfunctions in adolescent genetically modified mice. Thus, this automatic paradigm provides a further tool to assess attentional control in adolescent mice, and the development of dysfunctional executive functions from adolescence to adulthood.